Towards harmonized laboratory methodologies in veterinary clinical bacteriology: outcomes of a European survey - Koritnik, Tom; Cvetkovikj, Iskra; Zendri, Flavia; Blum, Shlomo Eduardo; Chaintoutis, Serafeim Christos; Kopp, Peter A.; Hare, Cassia; Štritof, Zrinka; Kittl, Sonja; Gonçalves, José; Zdovc, Irena; Paulshus, Erik; et al. (Frontiers in Microbiology, 2024)
Veterinary clinical microbiology laboratories play a key role in antimicrobial stewardship, surveillance of antimicrobial resistance and prevention of healthcare associated-infections. However, there is a shortage of international harmonised guidelines covering all steps of veterinary bacterial culture from sample receipt to reporting. In order to gain insights, the European Network for Optimization of Veterinary Antimicrobial Treatment (ENOVAT) designed an online survey focused on the practices and interpretive criteria used for bacterial culture and identification (C&ID), and antimicrobial susceptibility testing (AST) of animal bacterial pathogens. A total of 241 microbiology laboratories in 34 European countries completed the survey, representing a mixture of academic (37.6%), governmental (27.4%), and private (26.5%) laboratories. The C&ID turnaround varied from 1-2 days (77.8%) to 3-5 days (20%), and 6-8 days (1.6%), with similar timeframes for AST. Individual biochemical tests and analytical profile index (API) biochemical test kits were the most frequent tools used for bacterial identification (77% and 56%, respectively), followed by MALDI-TOF MS (46%). For AST, Kirby-Bauer disk diffusion (DD) and minimum inhibitory concentration (MIC) determination were conducted by 44% and 33% of laboratories, respectively, with a combination of EUCAST and CLSI clinical breakpoints (CBPs) preferred for interpretation of the DD (41.2%) and MIC (47.6%) results. In the absence of specific CBPs, laboratories used human CBPs (53%) or veterinary CBPs representing another body site, organism or animal species (51%). Importantly, most laboratories (47.9%) only report the qualitative interpretation of the result (S, R, and I). As regards testing for AMR mechanisms, 48.5% and 46.7% of laboratories routinely screened isolates for methicillin resistance and ESBL production, respectively. Notably, selective reporting of AST results (i.e. excluding highest priority critically important antimicrobials from AST reports) was adopted by 39.5% of laboratories despite a similar proportion not taking any approach (37.6%) to guide clinicians towards narrower-spectrum or first-line antibiotics. In conclusion, we identified a broad variety of methodologies and interpretative criteria used for C&ID and AST in European veterinary microbiological diagnostic laboratories. The observed gaps in veterinary microbiology practices emphasize a need to improve and harmonise professional training, innovation, bacterial culture methods and interpretation, AMR surveillance and reporting strategies.